Leading with stories: Andrew Cuomo, family narratives and authentic leadership. (June 2021) - Vásquez, Camilla
Abstract: The increasing mediatization of politics and government requires political actors to disclose aspects of their private and personal lives within their political communications. This article focuses on a sequence of personal narratives told by New York governor, Andrew Cuomo, in one of his daily press briefings during the early days of the COVID-19 crisis. I show how Cuomo enacted authentic leadership by mobilizing relational identities in a narrative segment. By telling three interconnected family stories, Cuomo provided evidence for his stay-at-home policy for New Yorkers during the pandemic. The performance of various relational identities in this narrative sequence helped construct Andrew Cuomo and his family members as ordinary citizens, making them relatable to viewers; at the same time, through the telling of these particular stories, Cuomo positioned himself as a trustworthy, effective leader and a prescient, reliable decision-maker. The study demonstrates how affective, relational discourse can be exploited by political leaders in the service of advancing their more transactional goals.